2016
DOI: 10.1111/head.13012
|View full text |Cite
|
Sign up to set email alerts
|

Structural Gray Matter Alterations in Chronic Migraine: Implications for a Progressive Disease?

Abstract: CM is associated with structural changes in brain regions involved in pain processing but also in affective and cognitive aspects of pain. Some GM alterations are correlated with headache frequency assessed in EM and CM. The findings support the assumption that chronic pain alters brain plasticity. GMV increase may reflect a remodeling of the central nervous system due to repetitive headache attacks leading to chronic sensitization and a continuous ictal-like state of the brain in chronic migraineurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 57 publications
4
72
4
1
Order By: Relevance
“…Contrary to the current findings, several studies have found more hippocampal volume in migraine patients and in patients with chronic pain relative to control populations. Hubbard et al 37 and Neeb et al 38 reported more hippocampal volume in migraine patients and more hippocampal volume was reported in a study that investigated the brain morphology in patients with burning mouth syndrome. 39 Results of a meta-analysis of chronic pain studies found the hippocampus to be the only region that had larger volumes in patients compared to controls.…”
Section: Discussionmentioning
confidence: 93%
“…Contrary to the current findings, several studies have found more hippocampal volume in migraine patients and in patients with chronic pain relative to control populations. Hubbard et al 37 and Neeb et al 38 reported more hippocampal volume in migraine patients and more hippocampal volume was reported in a study that investigated the brain morphology in patients with burning mouth syndrome. 39 Results of a meta-analysis of chronic pain studies found the hippocampus to be the only region that had larger volumes in patients compared to controls.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, repeated and long-term migraine attacks may induce functional and structural plastic changes that may underlie the progression of the disorder [8, 9]. Voxel-based morphometry (VBM) and surface-based morphometry (SBM) are advantageous for evaluating structural alterations (such as gray matter volume, cortical thickness and gyrification index [GI]) of the gray matter due to their ability to localize abnormal brain regions in patients without a priori hypothesis [1012].…”
Section: Introductionmentioning
confidence: 99%
“…It has repeatedly been demonstrated how the migraine brain differs morphologically from the healthy brain in several brain regions. Moreover, these alterations appear to progress over time and with attack frequency [25,28,[31][32][33][34][35]. However, there may well be alterations at the level of structural synaptic plasticity that cannot be detected in vivo in humans with available methods.…”
Section: Discussionmentioning
confidence: 99%
“…Results from these investigations have identified differences between control and migraine brains with regard to resting state activity and structure of gray and white matter. Differences have been detected in the frontal lobes, corpus callosum, the limbic system, cerebellum, the brainstem and nociceptive regions, although findings are not consistent across studies [22,24,25,[27][28][29][30][31][32][33][34][35][36]. In addition to regional differences, cortical thickness has been reported to differ between migraine patients and controls, and even correlate to attack frequency [37].…”
Section: Introductionmentioning
confidence: 94%